Functional Delayed Echolalia in Please Stand By: A Case Study of the Main Character - Zalukhu, Jun Ires Adeka; Robert Berkat Laia (Paradigma Lingua, 2025)
This research analyzes the functional delayed echolalia of Wendy, the main character in the film Please Stand By (2017), using Prizant and Rydell’s framework. Echolalia, the repetition of phrases or sentences, serves as a key communication tool for individuals with autism, aiding social interaction and emotional regulation. Employing a descriptive qualitative method, the study identifies and categorizes echolalic phrases from the film. The findings reveal seven types of interactive delayed echolalia (turn-taking, verbal completion, providing information, protest, request, affirmation, and directive) and four types of non-interactive delayed echolalia (non-focused, situational association, self-directive, and rehearsal). These results highlight echolalia’s functionality in supporting autistic individuals' communication and self-regulation. By analyzing how echolalia is portrayed in a media context, this study contributes to a deeper understanding of autism communication and promotes greater awareness of its significance in fostering social inclusion.